Calcium-magnesium composite fireproof flame-retardant material, preparation method and application thereof, flame-retardant optical / cable and preparation method thereof

By using calcium-magnesium composite fire-retardant flame retardant materials, combined with biomass calcium materials, magnesium hydroxide and VAE latex and other raw materials, the existing flame retardant packaging has been solved, the excellent flame retardant properties and mechanical strength of the material are achieved, and the production cost is reduced.

CN119552544AInactive Publication Date: 2025-03-04FUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411601437.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing flame retardant wraps are made of magnesium hydroxide as the main raw material, and the flame retardant efficiency is low, which affects the mechanical properties and processing properties of the wraps and cables.

Method used

Using calcium-magnesium composite fire-retardant flame retardant materials, materials with excellent flame retardant and mechanical strength are prepared by mixing raw materials such as biomass calcium materials, magnesium hydroxide and VAE latex in a specific proportion, and preparing them through drying and other steps.

Benefits of technology

It has achieved the improvement of flame retardant and mechanical properties of calcium-magnesium composite fire-retardant materials, while reducing production costs and being suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129244040000071
    Figure BDA0005129244040000071
Patent Text Reader

Abstract

The invention provides a calcium-magnesium composite fireproof flame-retardant material, a preparation method and application thereof, a flame-retardant optical / cable and a preparation method thereof, and relates to the technical field of flame-retardant materials. According to the invention, only water is used as a solvent, the VAE latex is used as a polymer matrix, the biomass calcium material powder and the magnesium hydroxide are used as fillers, the raw materials are low in price and easy to obtain, and the calcium-magnesium composite fireproof flame-retardant material has excellent flame retardance and mechanical strength. According to the invention, the layered structure, gas generation mechanism, stable thermal decomposition product and excellent mechanical property of the biomass calcium material are utilized, so that the flame retardant property and mechanical property of the calcium-magnesium composite fireproof flame-retardant material can be effectively improved. Through the synergistic effect of the magnesium hydroxide and the biomass calcium material, the flame retardant property, tensile strength and stretch rate of the calcium-magnesium composite fireproof flame-retardant material are enhanced. Moreover, the biomass calcium is solid waste, the raw materials are easy to obtain and low in price, and the calcium-magnesium composite fireproof flame-retardant material is low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant materials, and in particular to a calcium-magnesium composite fireproof and flame retardant material and a preparation method and application thereof, a flame retardant optical / cable and a preparation method thereof. Background Art

[0002] The application scenarios of optical (electrical) cables have put forward higher requirements for safety, flame retardancy and mechanical properties. At present, flame-retardant and fire-resistant communication optical (electrical) cables are composed of conductors, insulation layers, fire-retardant tapes, etc. The more mature flame-retardant tapes on the market use magnesium hydroxide as the main raw material. Due to the low flame retardant efficiency of magnesium hydroxide, the flame retardant effect can only be achieved when the filling amount reaches more than 60%, which affects the mechanical properties and processing properties of the tape and cable. Chinese patent CA118562200A points out that magnesium hydroxide has poor compatibility with polymers, the addition amount is limited, and it is difficult to ensure the mechanical properties of the composite material. Chinese patent CN114318910A1 discloses a processing step for a halogen-free low-smoke filling rope for cables, and the raw materials for preparing the raw materials include the following mass percentages: 30-60% magnesium hydroxide, 10-40% VAE emulsion, and the rest is water. However, although the above raw materials are coated with magnesium hydroxide, the mechanical properties and processing properties of the tape are not significantly improved. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a calcium-magnesium composite fireproof and flame-retardant material and its preparation method and application, flame-retardant optical / cable and its preparation method. The calcium-magnesium composite fireproof and flame-retardant material provided by the present invention has excellent flame retardancy and mechanical strength, and is low in cost.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The invention provides a calcium-magnesium composite fireproof and flame-retardant material. The raw materials for preparation include, by weight, 1 to 10 parts of biomass calcium material, 1 to 10 parts of magnesium hydroxide, 2 to 8 parts of VAE latex, and 10 to 30 parts of water.

[0006] Preferably, the biomass calcium material comprises one or more of shells, oyster shells and egg shells;

[0007] The biomass calcium material is crushed and then dried before use to obtain biomass calcium material powder;

[0008] The particle size of the biomass calcium material powder is 40 to 200 μm.

[0009] The present invention provides a method for preparing the calcium-magnesium composite fire-retardant material described in the above technical solution, comprising the following steps:

[0010] The prepared raw materials are mixed to obtain a mixed solution, and the mixed solution is dried to obtain a calcium-magnesium composite fireproof and flame-retardant material.

[0011] Preferably, the mixing comprises ultrasonic mixing or stirring mixing;

[0012] Preferably, the ultrasonic mixing time is 20 to 40 minutes and the power is 20 to 100W;

[0013] The stirring and mixing time is 30 to 90 minutes, and the speed is 200 to 800 r / min.

[0014] Preferably, the drying temperature is 60-100°C.

[0015] The present invention provides the use of the calcium-magnesium composite fireproof and flame-retardant material described in the above technical scheme or the calcium-magnesium composite fireproof and flame-retardant material prepared by the preparation method described in the above technical scheme in optical cable wrapping tape or electrical cable wrapping tape.

[0016] The invention provides a flame-retardant optical / electric cable, comprising a substrate and a calcium-magnesium composite fire-retardant material coated on the surface of the substrate; the substrate comprises an optical cable or an electric cable.

[0017] The present invention provides a method for preparing the flame-retardant optical / cable described in the above technical solution, comprising the following steps: mixing the raw materials for preparing the calcium-magnesium composite fire-retardant material described in the above technical solution to obtain a mixed liquid, coating the mixed liquid on a substrate and then drying to obtain a flame-retardant optical / cable.

[0018] Preferably, the mixing comprises ultrasonic mixing or stirring mixing;

[0019] The ultrasonic mixing time is 20 to 40 minutes, and the power is 20 to 100W;

[0020] The stirring and mixing time is 30 to 90 minutes, and the speed is 200 to 800 r / min.

[0021] Preferably, the drying temperature is 60-100°C.

[0022] The present invention provides a calcium-magnesium composite fireproof and flame-retardant material, and the raw materials for preparation include, by weight, 1 to 10 parts of biomass calcium material, 1 to 10 parts of magnesium hydroxide, 2 to 8 parts of VAE latex, and 10 to 30 parts of water. The present invention only uses water as a solvent, VAE latex as a polymer matrix, and biomass calcium material and magnesium hydroxide as fillers. The raw materials are low-priced and easy to obtain, and the calcium-magnesium composite fireproof and flame-retardant material has excellent flame retardancy and mechanical strength. Specifically, the present invention effectively combines the calcium-magnesium composite fireproof and flame-retardant material with glass fiber by adding VAE latex as a polymer matrix. The present invention enhances the flame retardant properties, tensile strength and elongation of the calcium-magnesium composite fireproof and flame-retardant material through the synergistic effect of magnesium hydroxide and biomass calcium material. Generally, biomass calcium is a unique layered structure constructed by calcium carbonate and organic molecules; at high temperatures, calcium carbonate can decompose into calcium oxide and carbon dioxide, releasing carbon dioxide gas and generating calcium oxide, carbon dioxide dilutes the combustion-supporting gas, thereby slowing down the combustion rate, and calcium oxide acts as a protective layer to isolate the transfer of heat and gas; the unique layered structure of biomass calcium material can give the material good strength and toughness. The present invention utilizes the layered structure, gas generation mechanism, stable thermal decomposition products and excellent mechanical properties of biomass calcium material to effectively improve the flame retardant properties and mechanical properties of calcium-magnesium composite fire-retardant materials. Moreover, biomass calcium is solid waste, the raw materials are easy to obtain and the price is low, and the cost of calcium-magnesium composite fire-retardant materials is low.

[0023] The preparation method of the calcium-magnesium composite fireproof and flame-retardant material provided by the present invention has a simple process flow, easily available and inexpensive raw materials, is environmentally friendly, has low production cost, and is suitable for industrial production. DETAILED DESCRIPTION

[0024] The invention provides a calcium-magnesium composite fireproof and flame-retardant material. The raw materials for preparation include, by weight, 1 to 10 parts of biomass calcium material, 1 to 10 parts of magnesium hydroxide, 2 to 8 parts of VAE latex, and 10 to 30 parts of water.

[0025] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0026] In terms of weight percentage, the raw materials for preparing the calcium-magnesium composite fire-retardant material provided by the present invention include 1 to 10 parts of biomass calcium material, and in a specific embodiment of the present invention, it can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0027] In the present invention, the biomass calcium material preferably includes one or more of shells, oyster shells and eggshells. In the present invention, the biomass calcium material is first crushed and then dried before use to obtain biomass calcium material powder. In the present invention, the particle size of the biomass calcium material is preferably 40 to 200 μm, and in a specific embodiment of the present invention, it can be 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.

[0028] The biomass calcium material used in the present invention has a unique layered structure constructed of calcium carbonate and organic molecules. At high temperatures, calcium carbonate can decompose into calcium oxide and carbon dioxide, releasing carbon dioxide gas and generating calcium oxide. Carbon dioxide dilutes the combustion-supporting gas, thereby slowing down the combustion rate, and calcium oxide acts as a protective layer to isolate the transfer of heat and gas. Moreover, the unique layered structure of the biomass calcium material can give the calcium-magnesium composite fire-retardant material good strength and toughness.

[0029] In the present invention, the pulverizing preferably includes ball milling pulverizing, and the ball milling pulverizing time is preferably 5 to 16 hours, and in a specific embodiment of the present invention, it can be 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours; the rotation speed of the ball milling pulverizing is preferably 200 to 700 r / min, and in a specific embodiment of the present invention, it can be 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min or 700 r / min.

[0030] In the present invention, the drying preferably includes one or more of room temperature drying, normal pressure heating drying, vacuum heating drying and freeze drying. In the present invention, the temperature of the room temperature drying is preferably room temperature, and the time is preferably 10 to 24 hours, and in specific embodiments of the present invention, it can be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours. In the present invention, the temperature of the normal pressure heating drying is preferably 50 to 80 degrees Celsius, and in specific embodiments of the present invention, it can be 50 degrees Celsius, 55 degrees Celsius, 60 degrees Celsius, 65 degrees Celsius, 70 degrees Celsius, 75 degrees Celsius or 80 degrees Celsius; the time of the normal pressure heating drying is preferably 5 to 12 hours, and in specific embodiments of the present invention, it can be 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours. In the present invention, the temperature of the vacuum heating drying is preferably 50 to 80°C, and in a specific embodiment of the present invention, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C; the time of the vacuum heating drying is preferably 5 to 12 hours, and in a specific embodiment of the present invention, it can be 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h. In the present invention, the temperature of the freeze drying is preferably -50 to -80°C, and in a specific embodiment of the present invention, it can be -50°C, -60°C, -70°C or -80°C; the time of the freeze drying is preferably 10 to 24h, and in a specific embodiment of the present invention, it can be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h.

[0031] The raw materials for preparing the calcium-magnesium composite fireproof and flame-retardant material provided by the present invention include 1 to 10 parts of magnesium hydroxide, based on the mass fraction of the biomass calcium material powder, and in a specific embodiment of the present invention, it can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. The present invention enhances the flame retardant properties, tensile strength and elongation of the calcium-magnesium composite fireproof and flame-retardant material through the synergistic effect of magnesium hydroxide and biomass calcium material.

[0032] The raw materials for preparing the calcium-magnesium composite fire-retardant material provided by the present invention include 2 to 8 parts of VAE latex, and in a specific embodiment of the present invention, the raw materials may be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, based on the mass fraction of the biomass calcium material powder. The present invention effectively combines the calcium-magnesium composite fire-retardant material with glass fiber by adding VAE latex as a polymer matrix.

[0033] The raw materials for preparing the calcium-magnesium composite fire-retardant material provided by the present invention include 10 to 30 parts of water, based on the mass proportion of the biomass calcium material powder. In a specific embodiment of the present invention, it can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts.

[0034] The present invention also provides a method for preparing the calcium-magnesium composite fireproof and flame-retardant material described in the above technical solution, comprising the following steps: mixing the preparation raw materials to obtain a mixed liquid, and drying the mixed liquid to obtain the calcium-magnesium composite fireproof and flame-retardant material.

[0035] In the present invention, the mixing preferably includes ultrasonic mixing or stirring mixing; the mixing temperature is preferably room temperature.

[0036] In the present invention, the time of the ultrasonic mixing is preferably 20 to 40 min, and in a specific embodiment of the present invention, it can be 20 min, 25 min, 30 min, 35 min or 40 min; the power of the ultrasonic mixing is preferably 20 to 100 W, and in a specific embodiment of the present invention, it can be 20 W, 30 W, 40 W, 50 W, 60 W, 70 W, 80 W, 90 W or 100 W.

[0037] In the present invention, the time of the stirring and mixing is preferably 30 to 90 minutes, and in a specific embodiment of the present invention, it can be 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, 60 minutes, 65 minutes, 70 minutes, 75 minutes, 80 minutes, 85 minutes or 90 minutes; the speed of the stirring and mixing is preferably 200 to 800 r / min, and in a specific embodiment of the present invention, it can be 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, 650 r / min, 700 r / min, 750 r / min, 800 r / min, 850 r / min or 900 r / min. In the present invention, the stirring and mixing preferably includes magnetic stirring or mechanical stirring.

[0038] The present invention utilizes physical mixing to uniformly mix the biomass calcium material powder and the magnesium hydroxide, thereby avoiding the agglomeration of the magnesium hydroxide and the biomass calcium material powder, and enhances the flame retardant performance, tensile strength and elongation of the calcium-magnesium composite fire-retardant material through the synergistic effect of magnesium hydroxide and the biomass calcium material.

[0039] In the present invention, the drying temperature is preferably 60-100°C, and in a specific embodiment of the present invention, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 95°C, 90°C, 95°C or 1000°C; the drying time is preferably ≥2 min, more preferably 2-10 min, and in a specific embodiment of the present invention, it can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.

[0040] The present invention also provides the application of the calcium-magnesium composite fire-retardant material described in the above technical solution or the calcium-magnesium composite fire-retardant material prepared by the preparation method described in the above technical solution in optical cable tape or cable tape. The calcium-magnesium composite fire-retardant material provided by the present invention is prepared by ball milling, mixing, coating, and drying steps. The prepared calcium-magnesium composite fire-retardant material has excellent mechanical properties, flame retardant properties, and tensile strength, and the manufacturing process is simple, the raw materials are easily available, the environment is friendly, and the cost is low. It has a good application prospect as an optical cable tape or a cable tape.

[0041] The present invention provides a flame-retardant optical / electrical cable, comprising a substrate and a calcium-magnesium composite fire-retardant material coated on the surface of the substrate; the substrate comprises an optical cable or an electrical cable. In the present invention, the material of the substrate preferably comprises glass fiber cloth. The thickness of the calcium-magnesium composite fire-retardant material of the present invention is preferably 0.15 to 0.20 mm, and in a specific embodiment of the present invention, it can be 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm or 0.20 mm.

[0042] The present invention provides a method for preparing the flame-retardant optical / cable described in the above technical solution, comprising the following steps: mixing the raw materials for preparing the calcium-magnesium composite fire-retardant material described in the above technical solution to obtain a mixed liquid, coating the mixed liquid on a substrate and then drying to obtain a flame-retardant optical / cable.

[0043] In the present invention, the coating preferably includes coating on one side of the substrate and then drying, and then coating on the other side and then drying. The present invention has no special limitation on the coating, and a coating method well known to those skilled in the art can be used to obtain a calcium-magnesium composite fire retardant material with a thickness of 0.15 to 0.20 mm.

[0044] In the present invention, the mixing and drying conditions are the same as those of the aforementioned calcium-magnesium composite fire-retardant material, and will not be described in detail herein.

[0045] In order to further illustrate the present invention, the calcium-magnesium composite fire-retardant material and its preparation method and application, flame-retardant optical / cable and its preparation method provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0046] In the following examples and comparative examples, the preparation method of biomass calcium material powder is as follows: the biomass calcium material is placed in a planetary ball mill, water is added for ball milling, the ball milling time is 10 hours, the ball milling speed is 300r / min, and then freeze-dried at -50°C to constant weight (10 to 24 hours) to obtain a biomass calcium material powder with a particle size of 40 to 200 μm.

[0047] Example 1

[0048] Take 2.5 parts of oyster shell powder, 2.5 parts of magnesium hydroxide, 4 parts of VAE latex, and 20 parts of water, ultrasonically treat at a power of 100 W for 30 minutes, and then stir at 800 r / min for 1 hour in a magnetic stirrer to obtain a mixed solution; use a coater to apply the mixed solution on a glass fiber cloth, heat and dry it at normal pressure at 80°C for 5 minutes, then turn the glass fiber cloth over, repeat the above coating and drying, and obtain a fire-retardant tape based on oyster shell / magnesium hydroxide coating.

[0049] Example 2

[0050] Take 1.67 parts of oyster shell powder, 3.33 parts of magnesium hydroxide, 4 parts of VAE latex, and 20 parts of water, ultrasonically treat at a power of 100 W for 30 minutes, and then stir at 800 r / min for 1 hour in a magnetic stirrer to obtain a mixed solution; use a coater to apply the mixed solution on a glass fiber cloth, heat and dry at normal pressure at 80° C. for 5 minutes, then turn the glass fiber cloth over, repeat the above coating and drying, and obtain a fire-retardant tape based on oyster shell / magnesium hydroxide coating.

[0051] Example 3

[0052] Take 3.33 parts of oyster shell powder, 1.67 parts of magnesium hydroxide, 4 parts of VAE latex, and 20 parts of water, ultrasonically treat at a power of 100 W for 30 minutes, and then stir at 800 r / min for 1 hour in a magnetic stirrer to obtain a mixed solution; use a coater to apply the mixed solution on a glass fiber cloth, heat and dry it at normal pressure at 80°C for 5 minutes, then turn the glass fiber cloth over, repeat the above coating and drying, and obtain a fire-retardant tape based on oyster shell / magnesium hydroxide coating.

[0053] Example 4

[0054] Take 2.5 parts of shell powder, 2.5 parts of magnesium hydroxide, 4 parts of VAE latex, and 20 parts of water, ultrasonically treat at a power of 100 W for 30 minutes, and then stir at 800 r / min in a magnetic stirrer for 1 hour to obtain a mixed solution; use a coater to apply the mixed solution on a glass fiber cloth, heat and dry it at normal pressure at 80°C for 5 minutes, then turn the glass fiber cloth over, repeat the above coating and drying, and obtain a fire-retardant tape based on shell / magnesium hydroxide coating.

[0055] Example 5

[0056] Take 2.5 parts of eggshell powder, 2.5 parts of magnesium hydroxide, 4 parts of VAE latex and 20 parts of water, perform ultrasound at a power of 100 W for 30 minutes, and then stir in a magnetic stirrer at 800 r / min for 1 hour to obtain a mixed solution; use a coater to apply the mixed solution on a glass fiber cloth, apply it on the glass fiber cloth, heat and dry it at normal pressure at 80° C. for 5 minutes, then turn the glass fiber cloth over, repeat the above coating and drying, and obtain a fire-retardant tape based on an eggshell / magnesium hydroxide coating.

[0057] Comparative Example 1

[0058] The only difference from Example 1 is that magnesium hydroxide is replaced by an equal amount of oyster shell powder to obtain a fire-retardant tape based on oyster shell coating.

[0059] Comparative Example 2

[0060] The only difference from Example 1 is that the oyster shell powder is replaced by an equal amount of magnesium hydroxide to obtain a fire-retardant tape based on a magnesium hydroxide coating.

[0061] Test Example 1

[0062] Performance Evaluation

[0063] The flame retardancy, oxygen index, gram weight and mechanical properties of the tapes prepared in the examples and comparative examples were tested.

[0064] 1. Flame retardancy test

[0065] The oxygen index of the tape is measured in an oxygen index tester. Under specified conditions, the minimum oxygen concentration required for the material to burn with a flame in an oxygen-nitrogen mixed gas flow. The lower the oxygen index (LOI), the easier the material burns.

[0066] 2. Mechanical properties test

[0067] The tape was cut into strip samples of 250 mm × 40 mm and tested in a universal tensile testing machine at 50 mm / min.

[0068] Table 1 Performance test results of the tapes prepared in Examples 1 to 4 and Comparative Example 1

[0069]

[0070] As shown in Table 1, the oxygen index of the tapes prepared in Examples 1 to 4 and Comparative Example 1 all reached 100%, showing excellent flame retardancy. In particular, Example 1, which is compounded with oyster shells and magnesium hydroxide, shows the best comprehensive performance in terms of tensile strength, elongation, gram weight, thickness and other indicators while maintaining an oxygen index of 100%.

[0071] Table 2 Performance test results of the tapes prepared in Examples 4 to 6

[0072] sample Biomass Calcium Oxygen index / % Tensile strength / N Elongation / % <![CDATA[Grammage / (g / m 2 )]]> Thickness / mm Example 4 Oyster shell 100 492.7 3.97 216 0.16~0.17 Example 5 shell 78 420.18 3.5 219 0.19~0.21 Example 6 eggshell 80 425.5 3.31 211 0.18~0.20

[0073] It can be seen from Table 2 that the oxygen index of Examples 5 to 6 is slightly lower than that of Example 4, and the tensile strength, elongation, gram weight and thickness are also slightly lower than that of Example 4. Therefore, considering the performance of the prepared flame-retardant tape, Example 4 using oyster shell as the main raw material has the characteristics of high tensile strength, low gram weight and high flame retardancy.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A calcium-magnesium composite fire-retardant material, the raw materials for preparation of which include, by weight: 1-10 parts of biomass calcium material, 1-10 parts of magnesium hydroxide, 2-8 parts of VAE latex, and 10-30 parts of water.

2. The calcium-magnesium composite fire-retardant material according to claim 1, characterized in that: The biomass calcium material includes one or more of shells, oyster shells and egg shells; The biomass calcium material is crushed and then dried before use to obtain biomass calcium material powder; The particle size of the biomass calcium material powder is 40 to 200 μm.

3. The method for preparing the calcium-magnesium composite fire-retardant material according to claim 1 or 2 comprises the following steps: The prepared raw materials are mixed to obtain a mixed solution, and the mixed solution is dried to obtain a calcium-magnesium composite fireproof and flame-retardant material.

4. The preparation method according to claim 3, characterized in that: The mixing includes ultrasonic mixing or stirring mixing; The ultrasonic mixing time is 20 to 40 minutes, and the power is 20 to 100W; The stirring and mixing time is 30 to 90 minutes, and the speed is 200 to 800 r / min.

5. The preparation method according to claim 3, characterized in that: The drying temperature is 60-100°C.

6. Use of the calcium-magnesium composite fire-retardant material according to any one of claims 1 to 2 or the calcium-magnesium composite fire-retardant material prepared by the preparation method according to any one of claims 3 to 5 in optical cable tape or electrical cable tape.

7. A flame-retardant optical / electric cable, comprising a substrate and a calcium-magnesium composite fire-retardant material coated on the surface of the substrate; the substrate comprises an optical cable or an electrical cable.

8. The method for preparing the flame-retardant optical / electrical cable according to claim 7, comprising the following steps: The raw materials for preparing the calcium-magnesium composite fireproof and flame-retardant material according to any one of claims 1 to 2 are mixed to obtain a mixed liquid, and the mixed liquid is coated on a substrate and then dried to obtain a flame-retardant optical / electrical cable.

9. The preparation method according to claim 8, characterized in that: The mixing includes ultrasonic mixing or stirring mixing; The ultrasonic mixing time is 20 to 40 minutes, and the power is 20 to 100W; The stirring and mixing time is 30 to 90 minutes, and the speed is 200 to 800 r / min.

10. The preparation method according to claim 8, characterized in that: The drying temperature is 60-100°C.

Citation Information

Patent Citations

  • Processing technology of halogen-free low-smoke filling rope for cable

    CN114318910A

  • Superfine magnesium hydroxide, preparation method thereof and polyethylene high-flame-retardant low-smoke halogen-free cable material

    CN118852735A

  • Wire cables with excellent fire resistance and flame retardancy

    JP1992036724U

  • Fire resistant material

    WO1983004041A1

  • Flame-retardant polyolefin composite material, and preparation method therefor and use thereof

    WO2023279660A1